The Role of Medium-Term Fiscal Frameworks for Transition Countries : The Case of Bulgaria - Horvath, Balazs; Szekely, Istvan (Washington, D.C. : International Monetary Fund, 2001)
This paper discusses the foundations for a medium-term fiscal framework for Bulgaria, a transition economy aspiring to join the European Union. The paper argues that a well-designed framework can help to enhance the credibility of macroeconomic policies and facilitate preparations for EU membership. It presents an illustrative scenario for Bulgaria, utilizing a broad concept of net public debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet